HLA Risk Alleles in Aromatic Antiepileptic Drug-Induced Maculopapular Exanthema - Shi, Yi-Wu; Wang, Jie; Min, Fu-Li; Bian, Wen-Jun; Mao, Bi-Jun; Mao, Yong; Qin, Bing; Li, Bing-Mei; Ou, Yang-Mei; Hou, Yun-Qi; Zou, Xin; Guan, Bao-Zhu; et al. (Frontiers in Pharmacology, 2021)
To characterize human leukocyte antigen (HLA) loci as risk factors in aromatic antiepileptic drug-induced maculopapular exanthema (AED-MPE). A case-control study was performed to investigate HLA loci involved in AED-MPE in a southern Han Chinese population. Between January 2007 and June 2019, 267 patients with carbamazepine (CBZ), oxcarbazepine (OXC), or lamotrigine (LTG) associated MPE and 387 matched drug-tolerant controls from 6 centers were enrolled. HLA-A/B/C/DRB1 genotypes were determined using sequence-based typing. Potential risk alleles were validated by meta-analysis using data from different populations and in silico analysis of protein-drug interactions. HLA-DRB1*04:06 was significantly associated with OXC-MPE (p = 0.002, pc = 0.04). HLA-B*38:02 was associated with CBZ-MPE (p = 0.03). When pooled, HLA-A*24:02, HLA-A*30:01, and HLA-B*35:01 additionally revealed significant association with AED-MPE. Logistic regression analysis showed a multiplicative interaction between HLA-A*24:02 and HLA-B*38:02 in CBZ-MPE. Meta-analysis of data from different populations revealed that HLA-24*:02 and HLA-A*30:01 were associated with AED-MPE (p = 0.02 and p = 0.04, respectively). In silico analysis of protein-drug interaction demonstrated that HLA-A*24:02 and HLA-A*30:01 had higher affinities with the three aromatic AEDs than the risk-free HLA-A allele. HLA-DRB1*04:06 showed relatively specific high affinity with S-monohydroxy derivative of OXC. HLA-DRB1*04:06 is a specific risk allele for OXC-induced MPE in the Southern Han Chinese. HLA-A*24:02, possibly HLA-A*30:01, are common risk factors for AED-MPE. The multiplicative risk potential between HLA-A*24:02 and HLA-B*38:02 suggests that patients with two risk alleles are at greater risk than those with one risk allele. Inclusion of these HLA alleles in pre-treatment screening would help estimating the risk of AED-MPE.